Is good enough enough? In Memoriam Karsai Dániel - Szappanyos, Melinda; Vadál, Ildikó (POLARITIES, 2025)
The authors of this article wrote another paper when Dániel Karsai was still alive, before the European Court of Human Rights judgment in his case was delivered. This paper sought to explore the shortcomings of the Hungarian regulation of euthanasia, more specifically the contradictions and constitutional dilemmas between the Fundamental Law and other Hungarian legislation. After the publication of the article, the European Court of Human Rights delivered its judgment in the case of Dániel Karsai v. Hungary, which, in addition to a general presentation of the judgment, also provides an opportunity for the authors to examine their earlier findings in a broader context. The purpose of the analysis is twofold. On the one hand, it is worth seeing whether the contradictions and constitutional dilemmas of Hungarian law reach the Court of Justice, and whether the latter took them into account in its decision. On the other hand, it is also important to examine the arguments on the basis of which the Court has ruled that Hungary has not violated the European Convention on Human Rights. The persen article also responds to one of Dániel Karsai's last requests: to put this terrible situation at the service of science.